Syntheses, Spectral Characterization, and Antimicrobial Studies on the Coordination Compounds of Metal Ions with Schiff Base Containing Both Aliphatic and Aromatic Hydrazide Moieties - Dinesh Kumar; Silky Chadda; Jyoti Sharma; Parveen Surain (Bioinorganic Chemistry and Applications)
An EtOH solution of 3-ketobutanehydrazide and salicylhydrazide on refluxing in equimolar ratio forms the corresponding Schiff base, LH3 (1). The latter reacts with Mn(II), Co(II), Ni(II), Cu(II), Zn(II), Cd(II), Zr(OH)2(IV), MoO2(VI), and UO2(VI) ions in equimolar ratio and forms the corresponding coordination compounds, [M(LH)(MeOH)3] (2, M = Mn, Co, Ni), [Cu(LH)]2 (3), [M′(LH)(MeOH)] (4, M′ = Zn, Cd), [Zr(OH)2(LH)(MeOH)2] (5), [MoO2(LH)(MeOH)] (6), and [UO2(LH)(MeOH)] (7). The coordination compounds have been characterized on the basis of elemental analyses, molar conductance, spectral (IR, reflectance, 1H NMR, ESR) studies, and magnetic susceptibility measurements. They are nonelectrolytes in DMSO. The coordination compounds, except 3, are monomers in diphenyl. They are active against gram-positive bacteria (S. aureus, B. subtilis), gram-negative bacteria (E. coli, P. aeruginosa), and yeast (S. cerevisiae, C. albicans). 1 acts as a dibasic tridentate ONO donor ligand in 2–7 coordinating through its both enolic O and azomethine N atoms. The coordination compounds 2 and 3 are paramagnetic, while rest of the compounds are diamagnetic. A square-planar structure to 3, a tetrahedral structure to 4, an octahedral structure to 2, 6, and 7, and a pentagonal bipyramidal structure to 5 are proposed.